Metabolomic profile of glycolysis and the pentose phosphate pathway identifies the central role of glucose-6-phosphate dehydrogenase in clear cell-renal cell carcinoma - Lucarelli, Giuseppe; Galleggiante, Vanessa; Rutigliano, Monica; Sanguedolce, Francesca; Cagiano, Simona; Bufo, Pantaleo; Lastilla, Gaetano; Maiorano, Eugenio; Ribatti, Domenico; Giglio, Andrea; Serino, Grazia; Vavallo, Antonio; et al. (Oncotarget, 2015)
The analysis of cancer metabolome has shown that proliferating tumor cells require a large quantities of different nutrients in order to support their high rate of proliferation. In this study we analyzed the metabolic profile of glycolysis and the pentose phosphate pathway (PPP) in human clear cell-renal cell carcinoma (ccRCC) and evaluate the role of these pathways in sustaining cell proliferation, maintenance of NADPH levels, and production of reactive oxygen species (ROS). Metabolomic analysis showed a clear signature of increased glucose uptake and utilization in ccRCC tumor samples. Elevated levels of glucose-6-phosphate dehydrogenase (G6PDH) in association with higher levels of PPP-derived metabolites, suggested a prominent role of this pathway in RCC-associated metabolic alterations. G6PDH inhibition, caused a significant decrease in cancer cell survival, a decrease in NADPH levels, and an increased production of ROS, suggesting that the PPP plays an important role in the regulation of ccRCC redox homeostasis. Patients with high levels of glycolytic enzymes had reduced progression-free and cancer-specific survivals as compared to subjects with low levels. Our data suggest that oncogenic signaling pathways may promote ccRCC through rerouting the sugar metabolism. Blocking the flux through this pathway may serve as a novel therapeutic target.